Consumers' perceptions and attitudes toward hunted wild game meat in the modern world: A literature review. (December 2022) - Corradini, Annafrancesca; Marescotti, Maria Elena; Demartini, Eugenio; Gaviglio, Anna
Abstract: Hunted wild game meat (HWGM) has a complete nutritional profile, and its environmental impact is lower than farmed meat. However, HWGM derives from hunting, which often relates to consumers' ethical concerns. This review aims to clarify which variables are linked to consumers' perceptions and attitudes toward HWGM. Results highlight that the body of literature about this topic is growing, especially in Europe and U.S. Moreover, gender and residence seem to be good predictors of consumers' perceptions and attitudes toward HWGM. Furthermore, some positive drivers were detected. The positive attitude toward hunting and familiarity with hunting resulted to be linked to HWGM consumption. Conversely, food safety consumers' concerns represent one of the main barriers. Finally, the seasonality of the product and the relative lack of HWGM market supply represent barriers to its consumption. Our findings may assist stakeholders in defining targeted marketing strategies and policies. Highlights: Hunted wild game meat (HWGM) is gaining attention as an alternative animal protein. Variables related to consumers' perceptions and attitudes toward HWGM are explored. HWGM is positively perceived as a healthy and environmentally friendly. The barriers of consumption are low availability and perception of low food safety.